The determinants of airline networks in the island regions of Japan (International Journal of Business, Economics and Management, 2023)
This study aims to show the determinants of the airline’s networks in Japanese island regions. Transportation systems are generally needed for residents in island regions to maintain their livelihood. Meanwhile, it is also necessary for people who live in outside regions such as tourists. Therefore, the transportation systems would be significant to maintain both tourism industries and the social situations in many of islands in Japan. This study, first, applied the network analysis to verify the nexus of connections among the transportation network in island regions in Japan. Degree centrality was calculated, and the result shows that some islands which is well-known as the tourism destinations located in southern part of Japan obtained many of connections to other places including other islands, as well as the mainland. Then regression model with the result of network analysis was composed and estimated by maximum likelihood method. The outcome shows that the situations of island society such as aged problem and economy in the islands would be influenced to maintain the airlines, as well as the amount of tourism demand. From these results, this paper concluded that both internal situations of island society and the tourism demand would be important to maintain island’s transportation system.